Typological peculiarities of blood circulation influence on athletes cardiorespiratory system indices in terms of increasing power load - Fedorov, N. A.; Vanyushin, Y. S.; Elistratov, D. E. (The Russian Journal of Physical Education and Sport, 2018)
It is stated that the types of blood circulation influence the reaction of an organism during physical loads. At the same time, there are contradictory opinions concerning the cardiovascular system dependency on the peculiarities of blood circulation during physical load. The aim of the work is cardiorespiratory system indices determination among the athletes in terms of increasing power load depending on typological peculiarities of blood circulation. Materials. 105 men at the age of 18-35 took part in the experiment. According to HI (heart index) value athletes were divided into the groups according to the type of blood circulation. Research methods: In order to reveal CSV (cardiac stroke volume) differentiated rheogram was recorded. In order to define the indices of external respiration we used pneumotachograph; V.Kubichek- a physiological estimation of cardiorespiratory system state, mathematical research results handling. Results. It was revealed that hypokinetic type of blood circulation (HTB) is more efficient in case of the highest inotropic hear function. It is considered as the most effective mechanism of urgent MBV (minute blood volume) adaptation to a load. Threshold of an adequate hemodynamic reaction in the groups of athletes is conditioned by typological peculiarities of blood circulation. The value of MRV (minute respiration volume) in different groups was achieved by different combination of RR (respiratory rate) and RC (respiratory capacity) indices. Conclusion. It is stated that the types of cardiorespiratory system adaptation are influenced by typological peculiarities of blood circulation.